Diagnostic accuracy of whole slide imaging for cutaneous, soft tissue, and melanoma sentinel lymph node biopsies with and without immunohistochemistry. (6th June 2018) - Sargen, Michael R.; Luk, Kevin M.; Stoff, Benjamin K.; MacKelfresh, Jaime; Patrawala, Samit; Zhang, Chao; Gutman, David; Chen, Suephy C.
Abstract : Background: Diagnostic accuracy with whole slide imaging (WSI) for complex inpatient and outpatient dermatopathology cases with immunohistochemistry (IHC) is unknown. Methods: WSI (Leica Aperio AT2 Digital Pathology scanner, N = 151 cases) was performed for Emory inpatient and outpatient skin ( N = 105), soft tissue ( N = 30), and melanoma sentinel lymph node biopsies ( N = 16) collected between 2000 and 2016. Resultant images were uploaded to an online cloud storage system for review by 2 board‐certified dermatopathologists (reviewers 1 and 2) with greater than 5 years of dermatopathology experience and 1 dermatopathology fellow (reviewer 3). Results: Reviewers 1 (diagnostic accuracy = 97%) and 2 (diagnostic accuracy = 95%) demonstrated high diagnostic accuracy with WSI. Diagnostic accuracy was greater than 90% for inpatient biopsies, melanocytic lesions, melanoma sentinel lymph node biopsies, and cases with immunohistochemistry, but was slightly lower for soft tissue cases (reviewer 1 = 89%; reviewer 2 = 89%). The dermatopathology fellow (reviewer 3) demonstrated lower diagnostic accuracy (84%). Conclusions: Diagnostic accuracy with WSI for skin, soft tissue, and melanoma sentinel lymph node biopsies with and without immunohistochemistry was greater than 95% for 2 reviewers with greater than 5 years of dermatopathology experience. Professional experience signing out dermatopathology cases may impact diagnostic accuracy with WSI.